НЕБЛАГОПРИЯТНЫЕ ГЕОМОРФОЛОГИЧЕСКИЕ ПРОЦЕССЫ, ВОЗНИКАЮЩИЕ В СВЯЗИ С СОЗДАНИЕМ ПОДПОРНЫХ ГИДРОТЕХНИЧЕСКИХ СООРУЖЕНИЙ - Малик Л.К. (My University, 2003)
Hazardous geomorphic processes such as landslides and collapses of rocks into reservoir are described. They lead to formation of large waves and overflow, which in turn may cause dam destruction. Factors that may activate such processes, for instance seismicity, atmospheric conditions, karst phenomena, water level fluctuations, abrasion are characterized. Comparative evaluation of land losses caused by the breakdown of various reservoirs bank is given. Possible growth of exogenous processes due to descent of water in the reservoir of Saratov hydroelectric plant is discussed.
Keywords: 551.4.042:627.8